Standardized protocol for reproductive phenology monitoring of fucalean algae of the genus Cystoseira s.l. with potential for restoration - Rindi, Fabio; Vergés, Alba; Zuchegna, Irene; Bianchelli, Silvia; de Caralt, Sònia; Galobart, Cristina; Santamaría, Jorge; Martini, Francesco; Monserrat, Margalida; Orfanidis, Sotiris; Sitjà, Cèlia; Tsioli, Soultana; et al. (Frontiers in Marine Science, 2023)
Active marine restoration is strongly encouraged to prevent the loss of the valuable habitats formed by Cystoseira sensu lato species, since they enhance biodiversity and preserve ecosystem functions and services. Current restoration interventions are mainly based on recruitment enhancement methods by deploying bags with fertile receptacles in situ or by outplanting juveniles grown ex situ under laboratory conditions. These methods allow the recovery of endangered species avoiding the depletion of the donor populations. In all cases, a priori knowledge of the reproductive phenology and recruitment periods of the species to be restored is essential, since the success of restoration techniques relies on collecting fertile branches and the obtention and survival of recruits. For their collection, identified donor populations characterized by dense Cystoseira s.l. cover should be studied. Specifically, monitoring the reproductive phenology of populations is crucial to detect the period of the year in which they develop mature reproductive structures and to understand how it might be linked to environmental conditions. Then, these general patterns on the reproductive phenology of Cystoseira s.l. species are essential to determine the most suitable time and conditions to plan for the most effective restoration action. Here, we provide a cost-effective and friendly protocol that can be easily and widely implemented for all Cystoseira s.l. species. We pose that this protocol provides a standardized and useful methodology to understand the environmental factors driving the optimal periods for sampling fertile branches across the Mediterranean Sea, and thus it can be an essential tool to plan future restoration actions.